2004
DOI: 10.1200/jco.2004.08.061
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Positive Gastric Adenocarcinomas: A Distinct Clinicopathologic Entity With a Low Frequency of Lymph Node Involvement

Abstract: EBV-carrying gastric adenocarcinomas are a distinct entity of carcinomas, characterized not only by unique genomic aberrations, but also by distinct clinicopathologic features associated with significantly better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
215
6
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(255 citation statements)
references
References 32 publications
29
215
6
5
Order By: Relevance
“…Although previous studies of EBV DNA in gastric tumour tissue and survival have produced inconsistent results (Chang et al, 2001;Lee et al, 2004), some have found improved survival associated with EBV, at least in subgroups (Koriyama et al, 2002;Lee et al, 2004;van Beek et al, 2004). Our association between high EBNA titres and improved survival was also limited to a subgroup, cardia cancers, although this finding may be due to chance.…”
Section: Discussionmentioning
confidence: 61%
“…Although previous studies of EBV DNA in gastric tumour tissue and survival have produced inconsistent results (Chang et al, 2001;Lee et al, 2004), some have found improved survival associated with EBV, at least in subgroups (Koriyama et al, 2002;Lee et al, 2004;van Beek et al, 2004). Our association between high EBNA titres and improved survival was also limited to a subgroup, cardia cancers, although this finding may be due to chance.…”
Section: Discussionmentioning
confidence: 61%
“…33 This group also had trend towards better survival, consistent with the reported literature. 23,32,[34][35][36] A significant association with the immunecheckpoint pathway protein programmed death ligand (PD-L1) was seen in the EBV gastric cancer cluster. Similar findings have been noted at genomic levels with amplification of the 9p24.1 locus, which includes the CD274 gene (encoding for PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…EBV-associated gastric adenocarcinoma (AC) accounts for up to 10% of gastric cancers and is associated with male gender, development in gastric stumps and favorable outcome. 1 Recently, a particularly high prevalence (27%) of EBV infection has been found in proximally located gastric carcinomas, especially in AC of the gastric cardia. 1,2 Cardiac AC shares a number of characteristic features with AC of the esophagus, i.e., profound male predominance, rising incidence and etiologic association with chronic gastroesophageal reflux.…”
mentioning
confidence: 99%
“…1 Recently, a particularly high prevalence (27%) of EBV infection has been found in proximally located gastric carcinomas, especially in AC of the gastric cardia. 1,2 Cardiac AC shares a number of characteristic features with AC of the esophagus, i.e., profound male predominance, rising incidence and etiologic association with chronic gastroesophageal reflux. 3 Both tumor types are therefore regarded as one clinical entity by some authorities.…”
mentioning
confidence: 99%